Synthesis and Binding Properties of a Tren‐Capped Hexahomotrioxacalix[3]arene. Issue 1 (11th December 2019) - Zahim, Sara; Ajami, Daniela; Laurent, Pascal; Valkenier, Hennie; Reinaud, Olivia; Luhmer, Michel; Jabin, Ivan
Abstract: The straightforward synthesis of a new hexahomotrioxacalix[3]arene‐based ligand capped by a tren subunit was developed and the binding properties of the corresponding zinc complex were explored by NMR spectroscopy. Similarly to the closely related calix[6]tren‐based systems, the homooxacalixarene core ensures the mononuclearity of the zinc complex and the metal center displays a labile coordination site for exogenous guests. However, very different host–guest properties were observed: i) in CDCl3, the zinc complex strongly binds a water molecule and is reluctant to recognize other neutral guests, ii) in CD3 CN, the exo‐coordination of anions prevails. Thus, in strong contrast to the calix[6]tren‐based systems, the coordination of neutral guests that thread through the small rim and fill the polyaromatic cavity was not observed. This unique behaviour is likely due to the fact that the 18‐membered ethereal macrocycle is too small to let a molecule threading through it. This work illustrates the key role played by the second coordination sphere in the binding properties of metal complexes. Abstract : Second coordination sphere matters : A hexahomotrioxacalix[3]arene‐based ligand capped by a tren subunit was synthesized. The corresponding zinc complex displays unique coordination and host‐guest properties, highlighting the crucial role played by the second coordination sphere in the recognition properties of metal complexes.